Ethical practices of the Dentistry theses of a public university in southern Peru (2016-2023) - Peñaloza de La Torre, Ulises Massino; Zevallos Cárdenas, Maricielo; Valdivia Silva, Carlos Enrique; Pezo Jiménez, Omar (Acta Bioethica, 2025)
The objective of the present research was to determine the ethical practices in the dentistry theses of a Public University in Southern Peru between 2016 and 2023, to improve ethical practices in dental research and promote a more responsible academic environment. The method used was quantitative, descriptive, and retrospective, utilizing public data from 150 theses in the institutional repository of the National University Jorge Basadre Grohmann. The variables analyzed included ethics in data collection, data manipulation, collaboration and authorship, and dissemination of results. The data were analyzed using descriptive statistics with IBM SPSS Statistics version 26. The findings show that 100% of the theses were not reviewed by an ethics committee, 52.2% did not present an execution certificate from the institution, 67% adequately recognized the contributions of advisors and collaborators, and 100% did not communicate the results to the study population. Additionally, most of the theses (91.3%) were of a basic type, which contrasts with the university policy that promotes applied research. The ethical practices in the dentistry theses of this university are deficient, especially in ethical review and result dissemination. It is recommended that ethical training be strengthened and agreements established with recognized ethics committees to ensure integrity and responsibility in research.